Internationalising higher education curricula for sustainable development: considerations for indigeneity and (inter)culturality - Mbah, MF; Clifton, N; Kushnir, I (Springer, 2024)
Higher Education (HE) can play a fundamental role in the achievement of sustainable development, and particularly the Sustainable Development Goals (SDGs) as captured in the Incheon declaration. However, what approach HE should take in this mission is a contested space. In this paper, we interrogate the idea of indigeneity. The pursuit to ascertain how an indigenised approach to internationalisation can support or enhance the contribution of HE curricula towards sustainable development is driven by the understanding that for sustainable development to be achieved at all, the process of knowledge creation must strive to make integral those epistemologies that exist beyond the “West”; an understanding that aligns, in particular, with Target 7 of the United Nations (UN) SDG 4 and seeks to empower victims of epistemic violence. In doing so, we employed a bibliographic research which captured a dual approach consisting of a bibliometric analysis of literature and a review of case studies. The findings from both methods suggest that internationalisation appears in different disciplinary contexts, but these are not always aligned with indigenisation. We maintain that the construct of (inter)culturality can address aspects within the framework of indigeneity to boost the internationalisation of HE curricula and outcomes for sustainable development. Central to this are four factors, namely: the need for effective human engagement with (inter)cultural competence, medium/place of curricula interaction, the initiative form and the reach of the development.